English for Business Communication / A Short Course Consisting of Five Modules: Cultural Diversity and Socialising, Telephoning, Presentations, Meetings and Negotiations: Student's Book - Sweeney Simon (Cambridge University Press, 1997)
A short course for intermediate level students who need to improve their communicative ability. Introduction, Cultural Diversity, Building a Relationship, Culture and Entertainment, Telephoning, Could I Leave a Message?, Good to Hear from You Again!, Unfortunately there's a Problem..., Presentations, Planning and Getting Started, Image and Impact and Making an Impression, The Middle of the Presentation, The End is Near...this is the End, Meetings, Making Meetings Effective, Sorry to Interrupt but..., What Do You Mean by...?, Negotiations, Know What You Want, Getting What You Can, Not Getting What You Don't Want, File Cards.